Traditional Market Management Strategy (Case Study: Markets and Market Ciawi Jasinga In Bogor Regency) - Mahfuddin, Mahfuddin; Djamil, Masyhudzulhak; Santoso, Iman (Jurnal Manajemen, 2018)
The purpose of this study was (a) analyze the factors that affect the internal and external PD Tohaga market in the development of market management in Bogor, (b) formulate a development strategy selection market management, and (c) to establish priority in the development strategy of market management. The results, it is known under the total customer perceives PD Pasar Tohaga performance in managing the market is still low, while a high level of customer expectations. Strategis factors which became a major force and has the highest relative importance is the equity of local government through the budget and the availability of assets in the form of 24 traditional markets are ready to be developed. The main drawback strategic factor and has the highest relative importance is the large number of residents of Bogor Regency. Strategic factor threats that have the highest relative importance is the implementation of quality standards are difficult to meet in the retail traditional markets.